THE USE OF SINGLE SLOT SUBSTITUTION DRILLS IN WRITING A DESCRIPTIVE TEXT - Antonia, Tia; Rufinus, Albert; Susilawati, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe aim of this research is to improve students’ writing ability, especially in subject-verb agreement in simple present tense of a descriptive text. This research was conducted at the Grade Eight students of SMPN 22 Pontianak in academic year 2017/2018. In this research, the subject is class VIIIB that consists of 30 students. The researcher conducted a classroom action research. The data were collected by measurement technique. The tools of data collecting were observation checklist, field note, and test. Single slot substitution drills was used as the technique of improving writing ability in this research which was conducted in two cycles. The research findings showed that students’ individual score on the first cycle, there were 14 students of 30 students passed the test. On the second cycle, 23 students passed the test. The writing ability of a descriptive text of Grade Eight students of B class of SMPN 22 Pontianak in academic year 2017/2018 improved by single slot substitution drills technique. Keywords: Writing, descriptive text, single slot substitution drills.